Improving The Competitiveness of Polukids SMEs through Empowerment Programs based on Digital Promotion and Sustainable Fashion Design - Heriyati, Pantri; Hutadjulu, Dicky Maryoga; Ananda, Artha Sejati; Paramita, Ratna Dewi; Firmansyah, Almira; Andhini, Grasheli Kusuma (Universitas Trisakti, 2024)
This paper examines the impact of an empowerment program implemented for Polukids, a small to medium-sized enterprise (SME) specializing in children’s fashion and denim, supported by Binus University. The study addresses critical challenges faced by Polukids, including insufficient online presence, limited digital marketing expertise, and inconsistent product quality. Through the program, which involved targeted training, digital content creation, and social media promotion, Polukids aimed to enhance its market competitiveness and operational efficiency. The research evaluates the effectiveness of these interventions in improving Polukids' digital engagement and product standards. Key findings indicate that while the program led to significant improvements in online visibility and product quality, sustained support and adaptation to industry trends are essential for long-term success. This paper highlights the role of academic institutions like Binus University in facilitating SME development and provides practical insights into the application of empowerment programs in the fashion industry. The results offer valuable lessons for other SMEs seeking to leverage academic partnerships to address business challenges and drive growth.